Trends of Nature Education Research in China: A Scholarly Review - Li, Yue; Chan, Yun‐Wen; Tseng, Yu‐Chi (Integrative conservation, 2025)
Nature education, regarded in China as activities in nature that connect humans with nature, is gaining increasing interest. Research studies in this area are growing too. However, little has been synthesized to understand the overarching patterns. This review explored the current status and trends of nature education studies in China. We adopted the traditional narrative literature review approach to examine 87 articles relevant to nature education in China, published in both English and Chinese from 2014 to April 2024. Our findings showcase three types of articles that represent the trends of studies in nature education: philosophical, empirical, and practical articles. Philosophical articles mainly addressed North American and European theories, with a relatively few Chinese philosophies. Empirical articles focused on exploring the current status of people's perception of nature and nature education, relationships among different variables, nature education outcomes, and setting or curriculum analysis. Practical articles described theoretical and practical applications as well as regional development efforts. The study sheds light on future research directions: (1) exploring Chinese theories and traditional cultures to deepen and ground nature education in local contexts, (2) developing innovative interventions and measuring nature education outcomes, and (3) connecting research to practice to enhance the field of nature education in China. 在中国, 自然教育被视为在自然中开展、旨在促进人与自然联结的活动, 近年来受到日益广泛的关注且相关研究数量持续增长。然而, 针对整体研究格局的系统性综述仍较为匮乏。本研究探讨中国自然教育研究的现状与趋势。我们采用传统叙述性文献综述的方法, 梳理了2014年至2024年4月间以中文和英文发表的87篇相关文献。结果显示, 自然教育研究主要呈现三类文章:哲学类、实证类与实践类。哲学类文章多借鉴北美与欧洲的理论体系, 对中国本土哲学的探讨相对不足；实证类文章主要聚焦公众对自然与自然教育的认知现状、自然教育相关变量之间的关系、自然教育的成效, 以及场域或课程分析；实践类文章着重于理论与实践的结合及区域发展经验。基于综述结果, 本研究提出未来研究的三个方向: (1) 深入挖掘中国理论与传统文化, 将自然教育扎根于本土情境； (2) 开发创新性干预并评估自然教育成效； (3) 加强研究与实践的衔接, 推动中国自然教育的持续发展。 Nature education has been gaining increasing attention in China in both practice and research. However, little work has been done to examine the overarching patterns of nature education in the country. In this study, we reviewed the current status and trends of nature education by adopting a traditional narrative literature review approach to examine 87 articles between 2014 and April 2024. Our findings highlight three types of articles that reflect the prevailing research trends: philosophical, empirical, and practical. Philosophical articles primarily discussed North American and European theories, with only limited engagement with Chinese philosophies. Empirical studies examined topics such as public perceptions of nature and nature education, relationships among various factors, outcomes of nature education, and analyses of settings or curricula. Practical articles described both theoretical and applied initiatives, as well as regional development efforts. On the basis of these findings, we suggest future research directions: (1) exploring Chinese theories and traditional cultures to ground nature education in local contexts, (2) developing innovative interventions and assessing their outcomes, and (3) strengthening the connection between research and practice to advance nature education in China. Practitioner points 分析显示, 自然教育研究主要分为三类:哲学类、实证类与实践类。 建议深入探讨中国的理论与传统文化, 将自然教育立足于本土情境。 建议加强研究与实践的衔接, 推动中国自然教育的进步。 自然教育在中国的实践与研究正受到越来越多的关注。然而, 目前针对全国自然教育整体格局的研究仍然有限。本研究采用传统叙述性文献综述方法, 梳理了2014年至2024年4月间发表的87篇相关文献, 以探讨中国自然教育研究的现状与发展趋势。研究结果显示, 自然教育研究主要呈现三类文章, 反映了当前的主要研究趋势:哲学类、实证类与实践类。哲学类文章主要探讨北美与欧洲的理论, 对中国本土哲学的涉猎较少；实证类研究关注公众对自然与自然教育的认知、自然教育相关因素之间的关系、自然教育的成效, 以及场域或课程分析；实践类文章则描述了理论与实践相结合的举措及区域发展努力。基于这些发现, 我们提出未来研究方向: (1) 深入挖掘中国的理论与传统文化, 将自然教育扎根于本土情境； (2) 开发创新性干预并评估其成效； (3) 加强研究与实践的衔接, 以推动中国自然教育的持续发展。